Production of Corn: Effects of Manganese Application on Plant Parameters - Md Sarwar, Jahan; Nozulaidi, M; NurInani, M (2016)
Corn plants need a small amount of manganese (Mn) that plays an active role in plant metabolism. We determined plant parameters, relative water content (RWC), chlorophyll (Chl) content, Chl fluorescence, photosynthesis parameters, and yield parameters to justify the effects of Mn on corn plants. Different Mn concentrations (0, 0.2, 1.5 and 3 ppm) were applied as a foliar spray on leaves of corn plants. The Mn treatment increased plant’s height and leaf numbers. RWC, net photosynthesis rate (Pn) and photosynthetically active radiation (PAR), Chl content and Chl fluorescence increased in leaves of Mn-treated plants compared to that of Mn-untreated plants. In addition, Mn application increased the yield of corn plants. Taken together, the Mn concentration at 1.5 ppm as a foliar application might increase corn production.